Interaction between Cl- channels and CRAC-related Ca2+ signaling during T lymphocyte activation and proliferation - Wang Guan-lei; Qian Yan; Qiu Qin-ying; Lan Xiu-jian; He Hua; Guan Yong-yuan (Acta Pharmacologica Sinica, 2016)
Aim: To test the hypothesis that Cl– channel blockers affect T cell proliferation through Ca2+-release-activated Ca2+ (CRAC) signaling and examine the effects of the combination of a CRAC channel blocker and a Cl– channel blocker on concanavalin A (ConA; 5 mg/mL)-induced Ca2+ signaling, gene expression and cellular proliferation in human peripheral T lymphocytes. Methods: [3H]Thymidine incorporation, Fura-2 fluorescent probe, RNase protection assay, and reverse transcription-polymerase chain reaction were used. Results: The Cl– channel blocker 4,4'-diisothiocyanostilbene-2,2'-disulfonic acid (DIDS) inhibited ConAinduced Ca2+ influx, interleukin-2 mRNA expression and T lymphocyte proliferation in a concentration-dependent manner, and also enhanced the inhibitory effects of 1-{beta-[3-(4-methoxyphenyl)propoxyl]-4-methoxyphenethyl}-1H-imidazole (SK&F96365) on the above key events during T cell activation. A combination of DIDS (1 μmol/L) and SK&F96365 (1 μmol/L) significantly diminished ConAinduced ClC-3 mRNA expression by 64%, whereas DIDS (1 μmol/L) or SK&F96365 (1 μmol/L) alone decreased ConA-induced ClC-3 mRNA expression by only 16% and 9%, respectively. Conclusion: These results suggest that there is an interaction between CRAC-mediated Ca2+ signaling and DIDS-sensitive Cl– channels during ConA-induced T cell activation and proliferation. Moreover, the DIDSsensitive Cl– channels may be related to the ClC-3 Cl– channels.